Pembaharuan Dalam Manajemen Pelayanan Publik Daerah: Tantangan dan Peluang Dalam Desentralisasi Pemerintahan di Indonesia - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Nuansa Rahmadi (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Like other countries around the world, both developed and developing countries, Indonesia's local government performance is measured primarily through the provision of basic services. Despite efforts to improve the service represents a concrete manifestation of good governance to promote human development, local governments have struggled to overcome many challenges and limitations. In this paper, good governance focuses on motivation and progress that emerged by some districts in Indonesia in improving their management system for the creation of effective service. Local governments can benefit from the assistance in fostering reform, provide advocacy, facilitating groups of stakeholders in implementing the reform agenda, monitor performance, and initiate and replicate the results. A study showed that coaching should be a partnership between consultant and local governments to develop capacity and provide skills to local government. The creation of a market for consulting and advocacy services include networking and advocacy among professional bodies and practitioners, public oversight bodies and “watchdog” organizations and groups of non-governmental organizations (NGO’s). In addition, the need to develop the market for the instruments in accordance with capacity building, particularly government-assisted instruments.